1986
DOI: 10.1177/070674378603100408
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Attempters of Suicide Presenting at an Emergency Department

Abstract: As part of a study involving seven hundred and forty-seven (747) consecutive cases of self-injury presenting at the emergency department of an inner city hospital, data pertaining to a multiple attempt group of ninety-nine subjects were compared with the data pertaining to first attempters. All subjects were rated on Beck's Lethality Scales, Intent Scale and Hopelessness Scale. In addition, a standard interview was conducted to provide psychosocial information. Of the total suicide attempt population, 14% can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
33
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 8 publications
7
33
0
Order By: Relevance
“…Moreover, genetic vulnerability may also impact an individual's frequency of attempting suicide. Specifically, the CDC has identified a family history of suicide as a risk factor for eventual death by suicide and several studies have found that a family history of suicide and/or suicide attempt are more prevalent among individuals with more than one suicide attempt (Forman et al, 2004;Jeglic, Sharp, Chapman, Brown, & Beck, 2005;Reynolds & Eaton, 1986). Family psychopathology may also play a role in an individual having multiple suicide attempts versus a single attempt.…”
Section: Psychiatric Disordersmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, genetic vulnerability may also impact an individual's frequency of attempting suicide. Specifically, the CDC has identified a family history of suicide as a risk factor for eventual death by suicide and several studies have found that a family history of suicide and/or suicide attempt are more prevalent among individuals with more than one suicide attempt (Forman et al, 2004;Jeglic, Sharp, Chapman, Brown, & Beck, 2005;Reynolds & Eaton, 1986). Family psychopathology may also play a role in an individual having multiple suicide attempts versus a single attempt.…”
Section: Psychiatric Disordersmentioning
confidence: 99%
“…Other psychiatric risk factors of suicide also shown to be higher amongst individuals with more than one suicide attempt are depression (Filinto da Silva Cais et al, 2009;Forman et al, 2004;Reynolds & Eaton, 1986) and suicidal ideation (Filinto da Silva Cais et al, 2009;Forman et al, 2004). Such individuals may be postulated to have more difficulty coping with internal and external stressors resulting in increased levels of hopelessness, depression, and suicidal ideation and eventual suicide attempt(s).…”
Section: Psychiatric Factorsmentioning
confidence: 99%
See 3 more Smart Citations